Effect of Foot Reflexology on sleep quality among Autistic children in selected special schools - Ms. Amruta Gade; Dr Sreelekha Rajesh; Dr Agnes Arun Swamy (The Bioscan, 2025)
A study was conduced on autistic individuals who commonly face challenges with sleep due to difficulties in relaxation & irregular melatonin levels, impacting the child & their families. The feet reflexology has demonstrated benefits in addressing sleep problems, this study aimed to assess the effect of feet reflexology on sleep quality among autistic children. A quantitative research approach with a quasi-experimental pretest-posttest control group design was used, convened sampling was used for the study. The study findings reveled foot reflexology intervention led a significant improvement in sleep quality in the experimental group, with notable decrease in moderate sleep problems (P<0.0001) thereby the study suggest the effectiveness of foot reflexology.